Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.0676
|View full text |Cite
|
Sign up to set email alerts
|

Advanced search for the extension of unresolved TeV sources with H.E.S.S.

Abstract: The resolution power of current Imaging Atmospheric Cherenkov Telescopes is presently restricted to scales of a few arcminutes. In the very high-energy (VHE; E > 100 GeV) gamma-ray regime, the measurement of source sizes that are comparable to or smaller than the resolution of the instrument is usually limited by statistics and in particular by the uncertainties in the characterisation of the instrument Point Spread Function (PSF). The PSF varies strongly with observation and instrument conditions demanding ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…It is also in accordance with the extension recently reported by the H.E.S.S. collaboration (Holler et al 2017). Furthermore, we have found evidence for extended γ-ray emission toward three SFRs (NGC 7822, NGC 1579, andIC 1396).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is also in accordance with the extension recently reported by the H.E.S.S. collaboration (Holler et al 2017). Furthermore, we have found evidence for extended γ-ray emission toward three SFRs (NGC 7822, NGC 1579, andIC 1396).…”
Section: Discussionsupporting
confidence: 93%
“…001 0 . 003 of the IC component of the nebula above energies of 700 GeV (Holler et al 2017 SFRs are found in giant molecular clouds. These clouds collapse and produce stars of all spectral types, some of which are massive O-and B-type stars.…”
Section: Crab Nebula (Fhesj05345+2201)mentioning
confidence: 99%
“…The resolution power of current Imaging Atmospheric Cherenkov Telescopes is presently restricted to scales of a few arc-minutes, and is limited first by statistics and second by the uncertainties in the characterisation of the instrument Point Spread Function (PSF). A new paradigm for the simulation of IACTs has been developed during the last years [15], aiming at overcoming the limitations of current approaches, and to more efficiently cover the simulation phase space. Indeed with the advent of hybrid systems consisting of a large number of IACTs with different sizes, types, and camera configurations, the complexity of the interpolation and the size of the phase space becomes increasingly prohibitive.…”
Section: Resolving Sources Down To Arcmin Scalementioning
confidence: 99%
“…Using the RWS simulation scheme,the extension of the Crab nebula at TeV gamma-ray energies was resolved for the first time [16], with a width of 52 assuming a Gaussian source shape (Fig. 2).…”
Section: Resolving Sources Down To Arcmin Scalementioning
confidence: 99%
“…Using a very detailed (observation run-wise) simulation of the point spread function (psf) of the instrument, it could now be shown with H.E.S.S. data that sub-psf extensions can reliably be resolved, and that an intrinsic VHE source width of σ 52 fits the Crab data best, with the measured σ being significantly incompatible with zero [22].…”
Section: The Vhe Size Of the Crab Nebulamentioning
confidence: 99%